QUALITY IMPROVING GRAPH MODEL AND METHOD FOR Software requirements specification - A. U. Chirkova; V. V. Bakhtizin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The graph model for software requirements specification is proposed. Besides, there are possible actions of improving the quality characteristics of software requirements described. In total proposed model and actions represent a method of the quality improvement of the software requirement specification.